Cost of peritoneal dialysis and haemodialysis across the world - Karopadi, Akash Nayak; Mason, Giacomo; Rettore, Enrico; Ronco, Claudio (Nephrology, dialysis, transplantation, 2013)
Peritoneal dialysis (PD) as a modality is underutilized in most parts of the world today despite several advantages including the possibility of it being offered in the remotest of locations and being significantly more affordable than haemodialysis (HD) in most cases. In this article, we will compare the cost of HD and PD in several countries to demonstrate that PD is less than, or at least as expensive as, HD. A thorough literature survey of EMBASE and PUBMED was conducted; 78 articles which compared the annual PD and annual HD costs were finally selected. Careful attention was paid to the methodology followed by each study and the year it was published in. Our final calculations included 46 countries (20 developed and 26 developing). We found that the cost of HD was between 1.25 and 2.35 times the cost of PD in 22 countries (17 developed and 5 developing), between 0.90 and 1.25 times the cost of PD in 15 countries (2 developed and 13 developing), and between 0.22 and 0.90 times the cost of PD in 9 countries (1 developed and 8 developing). From our analysis, it is evident that most developed countries can provide PD at a lesser expense to the healthcare system than HD. The evidence on developing countries is more mixed, but in most cases PD can be provided at a similar cost where economies of scale have been achieved, either by local production or by low import duties on PD equipment.